Protestant bodies: gesture in the English reformation - Hunt, Arnold 19XX- (Cambridge studies in early modern British history, 2025)
"What did early modern English Protestant worshippers think that they were doing when they bowed, knelt, or made the sign of the cross? Protestant Bodies explores the history of the English Reformation through the gestures of public worship and reestablishes their central role in early modern England"